Magnetic Properties Engineering of Nanopatterned Cobalt Antidot Arrays - Escrig-Murua, J; Palma-Solorza, J (Institute of Physics Publishing, 2016)
We report on the study of arrays of 60 nm wide cobalt antidots, nanopatterned using focused ion beam milling. Square and hexagonal symmetry arrays have been studied, with varying antidot densities and lattice constant from 150 up to 300 nm. We find a strong increase of the arrays magnetic coercivity with respect to the unpatterned film, which is monotonic as the antidot density increases. Additionally, there is a strong influence of the array symmetry to the in-plane magnetic anisotropy: square arrays exhibit fourfold symmetry and hexagonal arrays exhibit sixfold symmetry. The above findings are corroborated by magnetic imaging and micromagnetic modeling, which show the magnetic structure of the arrays to depend strongly on the array morphology. © 2016 IOP Publishing Ltd.